탈단백 소뼈 기질과 다양한 종류의 흡수성 막을 이용한 상악동 거상술 후의 조직-형태학적 분석 - 장태화(Tae-Hwa Jang); 장윤제(Yoon-Je Jang); 권대근(Tae-Geon Kwon); 이상한(Sang-Han Lee) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2007)
Purpose: The aim of the present study was to evaluate the effect of Bio-Oss on bone formation in terms of healing period and type of membrane so that determine the most suitable condition for implant fixation in grafted maxilla. Material & Method: Forty-five biopsy specimens from graft site were evaluated. Sinus lift was performed in the patients with reduced alveolar bone height(less than 5mm). The specimen was taken at the time of implant fixation, which was performed at least 5 months after the sinus lift procedure. All specimens were stained with H&E and Trichrome staining and evaluated histomorphometrically. Result: The results showed that Bio-Oss particle was in direct contact with newly formed bone in all cases. In the present study, the amount of newly formed bone and the residual bone substitute material were not statistically different according to various membrane and different healing period. There was no difference between the histological feature of the specimen of 5 and 31 months. No statistical significance was detected between male and female. Conclusion: The result implies that Bio-Oss does not seem to be resorbed over time regardless of the type of the membranes. The further investigation is needed to clarify this issue with the extended period of follow-up. KCI Citation Count: 0